Recovery of Small-Sized Blood Vessels in Ischemic Bone Under Static Magnetic Field - Xu, Shenzhi (Oxford University Press, 2007)
Effects of static magnetic field (SMF) on the vascularization in bone were evaluated using an ischemic bone model, where rat femoral artery was ligated. Magnetized and unmagnetized samarium–cobalt rods were implanted transcortically into the middle diaphysis of the ischemic femurs. Collateral circulation was evaluated by injection of microspheres into the abdominal aorta at the third week after ligation. It was found that the bone implanted with a magnetized rod showed a larger amount of trapped microspheres than that with an unmagnetized rod at the proximal and the distal region (P < 0.05 proximal region). There were no significant differences at the middle and the distal region. This tendency was similar to that of the bone mineral density in the SMF-exposed ischemic bone.